INNV-01. DRAMATIC RESPONSE OF ERBB2 POSITIVE BRAIN METASTASES FROM LUNG ADENOCARCINOMA TO FAM-TRASTUZUMAB DERUXTECAN-NXKI. (14th November 2022) - Thompson, Tracy; Luster, Sara; Savvides, Panayiotis; Sio, Terence; Westerlund, Lynsey; Fortin-Ensign, Shannon; Mrugala, Maciej
Abstract: BACKGROUND: In May 2022 the Food and Drug Administration approved fam-trastuzumab deruxtecan-nxki (FAM-TRAS) for adult patients with unresectable or metastatic Her-2 positive breast cancer who have received prior Her-2-based regimen and developed recurrence withing 6 months of completing therapy. Efficacy of the drug was established in the DESTINY-BreastO3 study. It has been suggested that fam-trastuzumab deruxtecan crosses blood-brain barrier, similarly to trastuzumab and another drug conjugate trastuzumab-DM1. CNS responses in patients with Her2 positive metastatic breast cancer have been reported. ERBB2 is a receptor tyrosine kinase from the family of EGFR/ERBB/HER family of kinases and its alterations can serve as a biomarker and actionable target in solid tumors. Here we present a case of CNS metastases from ERBB2 positive lung adenocarcinoma treated successfully with FAM-TRAS alone. METHODS: Case report. RESULTS: 50 y old man presented with a persistent cough. CT chest showed RUL nodule and peribronchial lymphadenopathy. Biopsy was positive for adenocarcinoma. Molecular testing has shown ERBB2 exon20 insertion, TP53 pathogenic variant, PDL1 positive (1%), and BRACA1 mutation. The patient had a solitary brain metastasis at the time of the initial diagnosis. He was started on FAM-TRAS and CNS response was seen while lung disease progressed. He was switched to immunotherapy but developed pneumonitis and therapy was stopped. He subsequently developed innumerable brain metastases and was restarted on FAM-TRAS. After 2 doses, dramatic response in CNS was seen with lung disease was stable. CONCLUSIONS: This case demonstrates the critical importance of molecular testing in neuro-oncology in the era of novel systemic therapies, many with good blood-brain barrier penetration. Systemic therapies for brain metastases can be successfully implemented in the right clinical setting and they can allow for the deferral of radiotherapy. ERBB2 mutations can guide clinicians when choosing therapy for many solid tumors, including those with brain metastases.